The Effect of TNF-Alpha Gene Polymorphisms At -376 G/A, -806 C/T, and -1031 T/C on The Likelihood of Becoming a Non-Responder to Etanercept in A Sample of Iraqi Rheumatoid Arthritis Patients - Mohammed, Samer Imad; Munaf Hashim Zalzala; Gorial, Faiq Isho (Iraqi Journal of Pharmaceutical Sciences, 2022)
Tumor necrosis factor-alpha (TNF-α) antagonists’ therapy are expensive and has a non-responsive rate between 30% to 40% in rheumatoid arthritis patients. Genetic variation plays a vital role in the responsiveness to this type of therapy.The aim of this study is to investigate if the presence of genetic polymorphism in the TNF-α gene promoter region at locations -376 G/A (rs1800750), -806 C/T (rs4248158), and -1031 T/C (rs1799964) affects rheumatoid arthritis patient’s tendency to be a non-responder to etanercept. Eighty RA patients on etanercept (ETN) for at least six months were recruited from the Rheumatology Unit at Baghdad Teaching Hospital. Based on The European League Against Rheumatism response (EULAR) criteria, patients were divided into two groups: responders and non-responders. After polymerase chain reaction amplification of their DNA, the amplified DNA was sequenced by Sanger method to determine the polymorphisms at the positions -376G/A, -806 C/T, and -1031T/C. The results of this study found that equally Phi correlation and binary logistic regression analysis revealed a non-significant association for all genotypes in the three polymorphic sites with the tendency for being non-responder. Moreover, there was no significant difference in TNF-α mean level or the change in disease activity score for 28 joints (DAS28) after six months of etanercept therapy between all genotypes for each polymorphic site. The present study concludes that there was no correlation between the polymorphisms in the TNF-α promoter region at -376G/A, -806 C/T, and -1031T/C with the tendency for being non-responder to ETN.